(3JHUQI GdeHJOF hJPcQI GdefJgis - (3eMeO Hf ESMGb Hf eMeO Hf jhSa Hf Ydj Gdbhfhj GdQhej, UOQ GdOjf,J (B673 (3g` s
(3ChdgG (B:s
(3aEPG cGf eG bHdgG ef LfSgG cGf CKbd aLGR MPagG dKbdgG hGYde Cfg dGjLhR Cf jSJYed GdVejQ GdefaUd s
(3BNQgG (B:s
(3aUd hGdjGA JVZe ajeG bHdgG ef cdeJjf EPG EfaJM eG HdgG aGYQa Pdc hbS Ydjg JQTO Ef TGA Gddg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B30s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B338s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdfMhs